2007
DOI: 10.1177/0305735607068890
|View full text |Cite
|
Sign up to set email alerts
|

Beyond valence and activity in the emotional connotations of music

Abstract: A B S T R AC T In the scaling of emotions in general, and their application to music in particular, the valence (good/bad) and activity or arousal dimensions are ubiquitous. Naive intuition and critics' writings have assumed a greater profundity in music's ability to express emotions than this would imply. Five experiments were performed to show that music is capable of expressing a greater detail in emotional range than can be captured by these two dimensions. The basic paradigm had participants rank order se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 29 publications
(49 reference statements)
3
25
0
4
Order By: Relevance
“…3 and 6 can be interpreted using more than one affective dimension. This result is in line with previous works which found an inherent ambiguity in the relation between music and emotions [37]. It is worth to remember that the clusters and structures of Figs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…3 and 6 can be interpreted using more than one affective dimension. This result is in line with previous works which found an inherent ambiguity in the relation between music and emotions [37]. It is worth to remember that the clusters and structures of Figs.…”
Section: Discussionsupporting
confidence: 92%
“…In other words, given that the most variance is explained by the V-A plane, it is difficult to explain the residual variance finding significative correlation with other affective dimensions. To overcome this limitation, Collier [37] followed an experimental paradigm that enforces more subtle emotional distinctions. Listeners were asked to evaluate 10 musical selections in five different conditions: the first uses a set of affective adjectives from the entire V-A plane; the others ones use a set of adjectives belonging to only one quadrant of the V-A plane each time.…”
Section: Pointing Out Secondary Dimensionsmentioning
confidence: 99%
“…A description of emotional effects of music limited to valence and arousal gradations as basic dimensions of emotion (e.g., Russell, 2003;Watson, Wiese, Vaidya, & Tellegen, 1999) precludes assessment of the kind of qualitative differentiation required by the study of the emotional effects of music (Collier, 2007). Although we do not question that emotional ratings of music can, to an extent, be accounted for by arousal and valence dimensions, this result adds little to an understanding of those emotional qualities that make music's emotional effects so uniquely rewarding.…”
Section: Current Emotion Models: a Procrustean Bed Formentioning
confidence: 99%
“…Rather, they were asked to describe the music in emotional terms. A more recent characterization of basic dimensions of musical affect beyond valence and arousal was also based on listeners' perceptions of emotional connotations of the music, not on anything the listeners felt themselves (Collier, 2007). As pointed out by Sloboda (1992), "The relevance of these [earlier] studies to emotional experience, however, is not proven.…”
Section: Previous Research Into Musical Emotionsmentioning
confidence: 99%
“…Valence accounts for pleasantness and unpleasantness. This two-dimensional arousal-valence emotion model cannot very well distinguish finitely generated emotions by music such as calm and bored [Collier 2007]. Fontaine et al [2007] indicated that emotion was not only two-dimensional.…”
Section: Emotion Models In Previous Workmentioning
confidence: 99%